ANALISIS POSTUR TUBUH MAHASISWA TERHADAP KURSI DENGAN MEJA MENYAMPING MENGGUNAKAN METODE SURVEY GOTRAK - Ninis Febrian Yuliansya; Selvy Aurelyah Zain; Athifatun Nisa’ Zainiyah; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2023)
In addition to workers, students also often complain of pain in the skeletal muscles or what is commonly called GOTRAK. In this study, students are aimed at analyzing posture and complaints in students when studying using a chair with a sideways table in terms of writing. The survey that has been conducted shows high student complaints of 60% when using a chair with a sideways table. Keywords: GOTRAK, complaints, students